Fluoride Release from Restorative Materials - Basso,Gabriela Romanini (2011)
The aim of this study was to evaluate in vitro fluoride (F) release from 4 restorative materials (3M ESPE): Ketak Molar Easymix [KME - conventional glass ionomer cement (GIC)]; Rely-X luting 2 [RL2 - resin-modified GIC (RMGIC)]; Vitremer (VIT- RMGIC); and Filtek Z250 [Z250 - negative control]. Disc-shaped specimens were fabricated according to the manufacturer’s instructions and placed into 10 mL of reverse osmosis water at 37°C until the analyses were done using a liquid membrane for selective F ion electrode (Orion 710). F release was evaluated every 6 h in the first day and thereafter daily during 28 days (d). The results were analyzed statistically by two-way ANOVA and Tukey’s test (α=0.05). Mean F release and standard deviation values (in ppm) were: KME: 6 h- 0.34 ± 0.04; 24 h- 1.22 ± 0.30; 7 d- 0.29 ± 0.09; 14 d- 0.20 ± 0.04; 28 d- 0.16 ± 0.01; RL2: 6 h- 2.46 ± 0.48; 24 h-12.33 ± 2.93; 7 d- 1.37 ± 0.38; 14 d- 0.80 ± 0.13; 28 d- 0.80 ± 0.21; VIT: 6 h- 0.98 ± 0.35; 24 h- 4.35 ± 1.22; 7 d- 0.66 ± 0.23; 14 d- 0.40 ± 0.07; 28 d- 0.39 ± 0.08; Z250: 6 h- 0.029 ± 0.001; 24 h- 0.024 ± 0.009; 7 d- 0.023 ± 0.004; 14 d- 0.025 ± 0.001; 28 d- 0.028 ± 0.001. RL2 RMGIC released more F than the other materials in all periods. The greatest release of F occurred in the first 24 h.